Smitten kitchen every day : triumphant and unfussy new favorites - Perelman, Deb (Alfred A. Knopf, 2017)
Shares unfussy, foolproof recipes that yield indulgent, flavorful dishes, including such options as sticky toffee waffles, bacony baked pintos, beefsteak skirt steak salad, and chocolate peanut butter icebox cake.